Case Report: Gigantic Arteriovenous Femoral Fistula Following Cardiac Artery Catheterization - Russu, Eliza; Mureşan, Adrian Vasile; Kaller, Reka; Coşarcă, Cătălin Mircea; Arbănaşi, Eliza-Mihaela; Arbănaşi, Emil-Marian (Frontiers in Surgery, 2022)
Purpose To present the case of a patient with a 9-mm iatrogenic fistula between a branch of the right profunda femoris artery, aneurysmally dilated at 1.851cm, and the right femoral vein, successfully treated with open surgical ligation. Case Report A 70-years-old female was referred to the Vascular Surgery Clinic due to worsening cardiac failure symptoms during the previous year. The medical history included a diagnostic cardiac artery catheterism through a Seldinger technique one year and a half ago. A recent ultrasound described velocities characteristic for a high flow arteriovenous communication in the right groin. Two consecutive cardiology exams, performed at nine months from one another, showed a decrease of almost 21% in the ejection fraction of the left ventricle. An angiography was conducted with the hope of achieving effective percutaneous embolization. Unfortunately, that was not the case. An open repair was scheduled, as the option for a stent-graft deployment was overruled as being too risky, potentially closing several branches of the profunda femoris artery and not fully completing the orifice due to a complicated anatomical positioning. Under local anesthesia, an open ligation was performed in very hostile anatomical conditions. The patient had an uncomplicated evolution and was discharged on the third day, symptom-free. Conclusions Iatrogenic arteriovenous fistulas are rare. Clinical presentation diagnoses the case efficiently, vascular imaging being essential for surgical preparation. Though open repair is not the gold standard, there are cases not suitable for the endovascular approach. These patients are eligible for a surgical solution, not without technical challenges.